Finnish late adolescents' physical activity during COVID-19 spring 2020 lockdown - Ng Kwok; Koski Pasi; Lyyra Nelli; Palomäki Sanna; Mononen Kaisu; Blomqvist Minna; Vasankari Tommi; Kokko Sami (BioMed Central, 2022)
Background Physical activity (PA) is recognised as one of the leading and effective strategies to prevent non-communicable diseases that boosts the immune system to fight against diseases. Closures of schools, sport clubs and facilities because of COVID-19 reduced the opportunities to participate in PA. We aimed to examine physical activity levels of late adolescents, the contexts to be physical active and its changes during the spring 2020 lockdown. Methods A national representative sample of late adolescents in general upper secondary school (n = 2408, females = 64%, mean age = 17.2y, SD = 0.63) completed self-report online surveys on PA behaviours between March and June 2020. Multinominal logistic regression analyses were performed to identify correlates with PA, and decision tree analyses to ascertain the perceived changes on PA during lockdown based on sport club aspirations and levels of PA. Results Among the late adolescents, the distribution of PA frequency was 23% (0-2 days/week), 35% (3-4 days/week), 30% (5-6 days/week) and 12% (7 days/week), and differences between males and females were not statistically significant. Participation in both indoor and outdoor PA were 50 times more likely to report daily PA (OR = 54.28, CI = 15.16-194.37) than non-participation. A quarter of late adolescents were not part of a sports club, yet their PA levels increased. Although sports club members generally perceived they did less PA during lockdown, over a third of sport club members with competitive aspirations reported daily PA. Conclusions Overall, most late adolescents reported their PA levels decreased during lockdown. Findings from this study continue to demonstrate factors associated with PA in the context of the COVID-19 lockdown.